Burden of chronic kidney disease and rapid decline in renal function among adults attending a hospital-based diabetes center in Northern Europe - Esther O'Sullivan; John Ferguson; Andrew Smyth; Fidelma P Dunne; Tomás P Griffin; Md Nahidul Islam; Matthew D Griffin; Timothy O'Brien; Damian G Griffin; Deirdre Wall; Sean F Dinneen; Paula M O'Shea; et al. (BMJ Open Diabetes Research & Care)
Introduction This study aimed to determine the prevalence of diabetic kidney disease (DKD) and rapid renal function decline and to identify indices associated with this decline among adults attending a diabetes center in Northern Europe.Research design and methods This is a retrospective cohort study of 4606 patients who attended a diabetes center in Ireland between June 2012 and December 2016. Definition/staging of chronic kidney disease used the Kidney Disease: Improving Global Outcomes (KDIGO) 2012 classification based on data from the most recently attended appointment. Relevant longitudinal trends and variabilities were derived from serial records prior to index visit. Rapid renal function decline was defined based on per cent and absolute rates of estimated glomerular filtration rate (eGFR) change. Multiple linear regression was used to explore the relationships between explanatory variables and per cent eGFR change.Results 42.0% (total), 23.4% (type 1 diabetes), 47.9% (type 2 diabetes) and 32.6% (other diabetes) had DKD. Rapid decline based on per cent change was more frequent in type 2 than in type 1 diabetes (32.8% vs 14.0%, p<0.001). Indices independently associated with rapid eGFR decline included older age, greater number of antihypertensives, higher log-normalized urine albumin to creatinine ratio (LNuACR), serum alkaline phosphatase, thyroid stimulating hormone, variability in systolic blood pressure and variability in LNuACR, lower glycated hemoglobin, high-density lipoprotein cholesterol and diastolic blood pressure, and lack of ACE inhibitor/angiotensin receptor blocker prescription.Conclusions DKD (using the KDIGO 2012 classification) and rapid eGFR decline were highly prevalent among adults attending a hospital-based diabetes clinic in a predominantly Caucasian Northern European country. The burden was greater for adults with type 2 diabetes. Expected as well as potentially novel clinical predictors were identified.